miR-150-5p represses TP53 tumor suppressor gene to promote proliferation of colon adenocarcinoma - Liu, Fang (Sci Rep, 2019)
MicroRNAs (miRNAs) play a critical role in regulation of numerous biological processes and pathogenesis of a variety of diseases. In addition, miRNAs contribute to carcinogenesis by acting as oncogenic or tumor suppressive. Circulating miRNAs including miR-150-5p are associated with colorectal cancer progression, and the putative targets of miR-150-5p include tumor suppressor gene, TP53. Here we sought to investigate the role of miR-150-5p-TP53 signaling pathway in proliferation of colon cancer and to determine expression levels of miR-miR-150-5p and TP53 in colon adenocarcinoma and adjacent non-cancerous tissue samples, or in human colon adenocarcinoma cell lines. MTT assay was used to determine proliferation and apoptosis in cell lines. Furthermore, we used Western blot to determine levels of cell cycle regulators with anti-miR-150-5p or apoptosis with overexpression of TP53. Our results show that expression levels of miR-150-5p were significantly elevated in clinical specimens from cancer patients. We further showed that inhibition of miR-150-5p increased TP53, and in turn, suppression of proliferation of colon adenocarcinoma. Moreover, inhibition of miR-150-5p or overexpression of TP53 caused cell arrest or apoptosis in colon adenocarcinoma. Our results support that miR-150-5p-TP53 pathway plays an important role in regulation of proliferation, cell arrest, and apoptosis in colon cancer, and could be an attractive target for therapy.